+0  
 
0
318
2
avatar+272 

 Let f(x) = 2x + 7 and g(x) = 3x + c. Find c if (f @ g)(x) = (g @ f)(x) for all x.

 

Thanks :D

WhichWitchIsWhich  Nov 6, 2017

Best Answer 

 #1
avatar+7339 
+1

f(x)  =  2x + 7

g(x)  =  3x + c

 

f( g(x) )  =  f( 3x + c )  =  2( 3x + c ) + 7

 

g( f(x) )  =  g( 2x + 7 )  =  3( 2x + 7 ) + c

 

And we want to know what  c  is when  f( g(x)  )  =  g( f(x) )  . That is... when

 

2( 3x + c ) + 7  =  3( 2x + 7 ) + c           Distribute the numbers outside the parenthesees.

 

6x + 2c + 7  =  6x + 21 + c                   Subtract  6x  from both sides of the equation.

 

2c + 7  =  21 + c             Subtract  c  from both sides of the equation.

 

c  + 7  =  21                    Subtract  7  from both sides of the equation.

 

c  =  14

hectictar  Nov 6, 2017
 #1
avatar+7339 
+1
Best Answer

f(x)  =  2x + 7

g(x)  =  3x + c

 

f( g(x) )  =  f( 3x + c )  =  2( 3x + c ) + 7

 

g( f(x) )  =  g( 2x + 7 )  =  3( 2x + 7 ) + c

 

And we want to know what  c  is when  f( g(x)  )  =  g( f(x) )  . That is... when

 

2( 3x + c ) + 7  =  3( 2x + 7 ) + c           Distribute the numbers outside the parenthesees.

 

6x + 2c + 7  =  6x + 21 + c                   Subtract  6x  from both sides of the equation.

 

2c + 7  =  21 + c             Subtract  c  from both sides of the equation.

 

c  + 7  =  21                    Subtract  7  from both sides of the equation.

 

c  =  14

hectictar  Nov 6, 2017
 #2
avatar+92794 
+1

This is an interesting problem......thanks, hectictar......!!!!

 

cool cool cool

CPhill  Nov 6, 2017

13 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.